2001
DOI: 10.1034/j.1600-0501.2001.012003219.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of loading on the development of nerve fibers around oral implants in the dog mandible

Abstract: Occlusal forces cause stress which morphologically affects the supporting tissues of implants. The aim of this study was to examine the effects of occlusal forces on the distribution of neurofilament protein (NFP)-positive nerve fibers in the tissue of peri-implant bone. The bilateral 2nd, 3rd and 4th mandibular premolars and the 1st molars were extracted from three mongrel dogs. After 4 months of healing, 4 screw-type implants were inserted in the oral cavity. Three months after insertion, the implants on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
91
1
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(101 citation statements)
references
References 14 publications
4
91
1
2
Order By: Relevance
“…Nevertheless, as nerve fibers around osseointegrated implants regenerate within 1 or 2 weeks, 10 this study simulated reactions of regenerated nerve fibers contacting implants or any event resulting in intimate implant-nerve contact to some extent. Yet, the short-and longterm implant-nerve interactions need to be demonstrated, with particular emphasis to the nerve signaling process for neurofilament protein-, calcitonin gene-related peptide-, vasoactive intestinal polypeptide-, and neuropeptide Y-containing nerve fibers around implants.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Nevertheless, as nerve fibers around osseointegrated implants regenerate within 1 or 2 weeks, 10 this study simulated reactions of regenerated nerve fibers contacting implants or any event resulting in intimate implant-nerve contact to some extent. Yet, the short-and longterm implant-nerve interactions need to be demonstrated, with particular emphasis to the nerve signaling process for neurofilament protein-, calcitonin gene-related peptide-, vasoactive intestinal polypeptide-, and neuropeptide Y-containing nerve fibers around implants.…”
Section: Discussionmentioning
confidence: 98%
“…[12][13][14] Hence, endosseous implants frequently contact with nerve fibers running throughout the bone. 10,11 Information on the morphology of mechanoreceptors and exteroceptive function of neural endings around endosseous implants is scarce. Neuropeptide and catecholaminergic innervation of bone and periosteum [15][16][17] may play a role on osseoperception, but sound evidence is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Contrarily, for the bendingminimised loading some bone-to-muscle communication is also needed in order for the muscle to react not only on the motionmotivated stimulus but also on the bone loaded state. The authors are currently not aware of publications on such a control mechanism, but with certainty bones are highly innervated systems (Mach et al, 2002;Marenzana and Chenu, 2008;McCredie, 2007;Wada et al, 2001). Mach et al (2002) showed that, while periosteum had the greatest density of both sympathetic and sensory innervations per area, bone marrow followed by the mineralised bone had the greatest total number of neural fibres.…”
Section: Calculatedmentioning
confidence: 96%
“…Studies on implant loading have shown, however, that the sensory thresholds of an implant are 10-100 times higher than those of natural teeth (Muhlbradt et al, 1989;Jacobs and van Steenberghe, 1991;Hammerle et al, 1995). Although some nerve fibers were observed in the vicinity of osseointegrated implants, and suggested to be the key elements contributing to sensory responses of external mechanical loading (Wada et al, 2001;Ysander et al, 2001), these nerve fibers were present at quite a low density, resulting in a much higher sensory threshold than that of natural teeth (Muhlbradt et al, 1989;Jacobs and van Steenberghe, 1991;Hammerle et al, 1995). Without an efficient self-protective mechanism afforded by the periodontal ligament, excessive forces may be loaded on the implant, and may result in damage to peri-implant bone (Misch et al, 2005).…”
Section: Introductionmentioning
confidence: 99%